2004
DOI: 10.1016/j.nbd.2003.11.004
|View full text |Cite
|
Sign up to set email alerts
|

Frontotemporal dementia and mitochondrial DNA transitions

Abstract: Frontotemporal dementia (FTD) is the second most common type of primary degenerative dementia. Some patients present an overlap between Alzheimer's disease (AD) and FTD both in neuropathological and clinical aspects. This may suggest a similar overlap in physiopathology, namely an involvement of mitochondrial DNA (mtDNA) in FTD, as it has been associated to AD. To determine if mtDNA is involved in FTD, we performed a Polymerase Chain Reaction-Restriction Fragment Length Polymorphism (PCR-RFLP) analysis, specif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
5
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 42 publications
3
5
0
Order By: Relevance
“…Kösel et al [4] found in patients with Parkinson’s disease (PD) a known missense mutation at nucleotide 3338 of the NADH dehydrogenase subunit 1 (ND1) mtDNA gene that changes the amino acid valine to alanine. This mutation has previously been described by Chalmers et al [5] in a control subject, and it was absent in subsets of our PD [6] and frontotemporal dementia [7] patients. …”
Section: Introductionsupporting
confidence: 78%
See 1 more Smart Citation
“…Kösel et al [4] found in patients with Parkinson’s disease (PD) a known missense mutation at nucleotide 3338 of the NADH dehydrogenase subunit 1 (ND1) mtDNA gene that changes the amino acid valine to alanine. This mutation has previously been described by Chalmers et al [5] in a control subject, and it was absent in subsets of our PD [6] and frontotemporal dementia [7] patients. …”
Section: Introductionsupporting
confidence: 78%
“…PCR and RFLP of patient and control DNA samples were performed as described previously [6]. When a positive result was found, the fragments of mtDNA were sequenced as reported before [7] and sequences were compared with the revised Cambridge sequence of the human mitochondrial genome [13]. In order to verify if the PCR product was an amplification of mtDNA genes or nuclear pseudogenes, we also analyzed total cellular DNA isolated from ρ⁰ cells.…”
Section: Methodsmentioning
confidence: 99%
“…These results are in agreement with previous studies that have also demonstrated mitochondrial impairment activity in related diseases, such as AD, PD, ALS and tauopathies [32,85,86,87,88]. Moreover, our group has previously reported a complex I deficiency in a patient with FTLD [22]. Other studies have shown that alterations in the VCP gene induced mitochondrial uncoupling that has been observed in different neurodegenerative diseases [14].…”
Section: Discussionsupporting
confidence: 92%
“…A significant clinical and neuropathological overlap with AD [20] has been described, which may suggest similarities in pathophysiology, including the involvement of mitochondrial DNA (mtDNA) in FTLD, as previously suggested for AD [21,22,23,24]. …”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation